ANALYSIS AND DEVELOPMENT OF THE BUBBLE MODEL OF THE FORMATION STAGE OF HIGH-VOLTAGE BREAKDOWN OF THE WATER GAP - V. G. Zhekul (National Technical University "Kharkiv Polytechnic Institute", 2018)
Purpose. A high-voltage underwater electric explosion, realized by discharging a capacitor into a water gap, is characterized by three main stages: the stage of formation of the plasma channel, the channel stage and post-discharge one. Substantially, the channel, post-discharge stages and the efficiency of energy release in the channel and the increase in the hydrodynamic effect on the object being processed depend on the parameters of the stage of formation. The purpose of the work was to review the existing mechanisms for the formation of a high-voltage discharge channel with the analysis and development of a bubble model of the stage of formation of water gap breakdown. Methodology. We have applied the analysis of existing theories on the formation of a high-voltage discharge channel, the carrying out of electrophysical studies with the processing of the obtained data. Results. A review and analysis of modern concepts of pre-breakdown processes in a high-voltage electric discharge in a liquid showed that the «bubble» model of the ignition of a discharge is applicable at an electric field strength (36 – 180) kV/cm. We have further developed the bubble model of the stage of formation of high-voltage breakdown on the results of experimental studies of the electrical characteristics of the discharge in the aqueous electrolyte with increased hydrostatic pressure and minimum voltage providing ignition of the discharge. A qualitative description of three phases of the stage of formation of the plasma channel in the liquid electrolyte is proposed. Originality. We have further developed the bubble model of the stage of formation of high-voltage breakdown of the liquid electrolyte on the results of experimental studies of the electrical characteristics of the discharge in the aqueous electrolyte with increased hydrostatic pressure and minimum voltage providing ignition of the discharge. A qualitative variation of the resistance of the gap in the pre-breakdown stage of the discharge is considered. Practical value. Determination of the scientific basis for creating a methodology for calculating the pre-breakdown characteristics of an electric discharge to improve the efficiency of electric discharge devices.